Future trends in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infection: An in-depth review of newer antibiotics active against an enduring pathogen. (September 2017) - Bal, A.M.; David, M.Z.; Garau, J.; Gottlieb, T.; Mazzei, T.; Scaglione, F.; Tattevin, P.; Gould, I.M.
Highlights: Several new agents have recently been licensed for treatment of infections caused by MRSA. Combination of glycopeptides or daptomycin with a β-lactam is being investigated in clinical trials. A genomics-driven approach to drug development is being explored. Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) continues to be a major public health problem. Vancomycin and teicoplanin have been in clinical use for several decades but their drawbacks are well described. In the last 10 years, several antibiotics have been made available for clinical use. Daptomycin and linezolid have been extensively used during this period. Other agents such as ceftaroline, ceftobiprole, dalbavancin, oritavancin, tedizolid and telavancin have been approved by regulatory agencies since 2009. Many others, such as the newer tetracyclines, fluoroquinolones, oxazolidinones and pleuromutilins, are in various stages of development. In addition, an ongoing multicentre trial is investigating the role of combination of vancomycin or daptomycin with β-lactam antibiotics. This review discusses the role of the newer antibiotics, reflecting the views of the 6th MRSA Consensus Conference meeting of the International Society of Chemotherapy MRSA Working Group that took place in 2016.